Boat acceleration, temporal structure of the stroke cycle, and effectiveness in rowing - Kleshnev, V. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2010)
The purposes of the study were to explain the double peak in the boat acceleration during the drive phase, to analyse the temporal structure of the stroke cycle, and to find correlations between the temporal structure and the boat type, rower gender, stroke rate, force profile, and effectiveness of rowing. Measurements of the boat acceleration, boat velocity, handle force, oar angle, and velocity of body segments were made in competitive rowing boats using a telemetry system. The accelerations of the whole system and of the rower's centre of mass (CM) were derived and used to define the temporal structure of the stroke cycle. Six microphases were defined during the drive phase, and three microphases were defined during the recovery phase. The relative magnitudes of the accelerations of the boat and of the rower's CM switched twice during the drive phase. During the `initial rower's acceleration` and the `rower's acceleration` microphases, the acceleration of the rower's CM was higher and, during the `initial boat acceleration` and `boat acceleration` microphases, the acceleration of the boat was higher. The presence of the initial boat acceleration microphase is an important indicator of the effectiveness of a rower's technique.